(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article examines the nature of children’s speech corpora and the stages of formation of children’s speech corpora. In today’s rapidly developing world, the body is a universal resource that is becoming increasingly important in any field. If you look at the history of the development of corpora, the first corpora were created in the field of linguistics. Today, corpora continue to occupy their place not only in linguistics, but also in medicine, pedagogy and psychology. In addition, corpora have become an important phenomenon in the field of language teaching. Children’s speech corpora play a particularly important role in this regard. The article briefly touches on some corpora of children’s speech. The given corpora are among the most successful works of corpus linguistics in the field of corpora of children’s speech.